Measurement of Futsal Physical Test on Students of Junior High School Country Two North Indralaya Using Outdoor Laboratories in The Education Park (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Research Actual wellness is one of the states of being that should be claimed by everybody, in light of the fact that with a decent constitution can make individuals move well without encountering huge weariness. Good physical fitness is very important for junior high school students to perform well in both academic and extracurricular activities. because good physical fitness is required of every student. The physical health of futsal students at students junior high school country two north indralaya was the focus of this study. To perform at its best, one must be in excellent physical condition. The design of this study is descriptive and quantitative. Twenty futsal students from students junior high school country two north indralaya served as the study’s participants. In this study, a 50 meter running test was used to measure speed, a bleep test was used to measure endurance, a sit-up test was used to measure abdominal muscle strength, a vertical jump test was used to measure explosive power, and a Agility t-Tst test was used to measure arm muscle strength. The descriptive presentation method of data analysis was used in this study. derived from the futsal physical test measurements of students at students junior high school country two north indralaya, which showed that two students (or ten percent) were in the very good category, nine students (or 45 percent) were in the good category, nine students (or 45 percent) were in the moderate category, and zero students (or zero percent) were in the less category or the very less category. The good category of nine students and the sufficient category of nine students produced the highest numbers of results. Therefore, it is possible to draw the conclusion that the physical average of futsal students junior high school country two north indralaya is satisfactory